European Citizenship as Rights Claiming (Glocalism: Journal of Culture, Politics and Innovation, 2018)
European citizenship, which was once seen as the symbol of European integration, is increasingly perceived as an obstacle to self-government and a threat to national welfare. As European ruling classes fail to provide an adequate response to the tensions that arise from the wider trends of globalization, anti-political movements are gaining support. A significant part of European citizenry is aligning with parties that preach the restoration of national borders and the reinstatement of cultural identity as the source of sovereign power embodied in the nation state.Does the way forward reside in dissolving the European project or reducing the power held by European institutions? In this article, we suggest the opposite. We need to begin by recognizing the significance of European integration as an evolving political experience of immense magnitude.We need to emphasize that Europe today provides citizens with unique means to claim social, political and economic rights by going beyond the borders of their states, create alliances, invoke different conventions and treaties, and debate and contest dominant perspectives in front of diverse audiences. Ultimately, we need to utilize aEuropean citizenship that reinstates political power to citizens towards fostering fresh sentiments for a new form of integration.
Keywords: European citizenship; European integration; rights claiming; European institutions; political power